Disruption of a Hedgehog-Foxf1-Rspo2 signaling axis leads to tracheomalacia and a loss of Sox9(+) tracheal chondrocytes - Nasr, Talia (Dis Model Mech, 2021)
Congenital tracheomalacia, resulting from incomplete tracheal cartilage development, is a relatively common birth defect that severely impairs breathing in neonates. Mutations in the Hedgehog (HH) pathway and downstream Gli transcription factors are associated with tracheomalacia in patients and mouse models; however, the underlying molecular mechanisms are unclear. Using multiple HH/Gli mouse mutants, including one that mimics Pallister–Hall Syndrome, we show that excessive Gli repressor activity prevents specification of tracheal chondrocytes. Lineage-tracing experiments show that Sox9(+) chondrocytes arise from HH-responsive splanchnic mesoderm in the fetal foregut that expresses the transcription factor Foxf1. Disrupted HH/Gli signaling results in (1) loss of Foxf1, which in turn is required to support Sox9(+) chondrocyte progenitors, and (2) a dramatic reduction in Rspo2, a secreted ligand that potentiates Wnt signaling known to be required for chondrogenesis. These results reveal an HH-Foxf1-Rspo2 signaling axis that governs tracheal cartilage development and informs the etiology of tracheomalacia. This article has an associated First Person interview with the first author of the paper.